Blockade of lncRNA‐ASLNCS5088–enriched exosome generation in M2 macrophages by GW4869 dampens the effect of M2 macrophages on orchestrating fibroblast activation. Issue 11 (20th August 2019) - Chen, Jialin; Zhou, Renpeng; Liang, Yimin; Fu, Xiujun; Wang, Danru; Wang, Chen
Abstract : In hypertrophic scar (HS) formation, the type 2 immune response induces the alternatively activated macrophages (M2), which manipulate fibroblasts to differentiate into myofibroblasts with active biologic functions and proliferation. Myofibroblasts express α‐smooth muscle actin (α‐SMA) and synthesize and produce additional collagen type I and collagen type III, inducing HS formation. However, studies on the mechanism of M2 macrophage modulation are only based on the recognition of profibrotic factors such as TGF‐β1 secreted by macrophages. The influence of exosomes from M2 macrophages on scar formation is still unknown. Both M2 macrophages and myofibroblasts highly express glutaminases (GLSs). GLS is a critical enzyme in glutaminolysis and is important for M2 macrophage and fibroblast polarization. In this study, we found that in a TGF‐β1‐stimulated coculture system, a long noncoding RNA (lncRNA) named lncRNA‐ASLNCS5088 was enriched in M2 macrophage‐derived exosomes. This lncRNA could be transferred with high efficiency to fibroblasts and acted as an endogenous sponge to adsorb microRNA‐200c‐3p, resulting in increased GLS and α‐SMA expression. Pretreatment with GW4869, which impairs M2 macrophage exosome synthesis, ameliorated these pathologic changes in fibroblasts in vitro. Local injection in the late scar formation period with GW4869 reduced α‐SMA + fibroblasts and alleviated the fibrosis of tissue after wound healing in vivo. —Chen, J., Zhou, R., Liang, Y., Fu, X., Wang, D., Wang, C. Blockade of lncRNA‐ASLNCS5088–enriched exosome generation in M2 macrophages by GW4869 dampens the effect of M2 macrophages on orchestrating fibroblast activation. FASEB J. 33, 12200–12212 (2019). www.fasebj.org